Musculoskeletal health in the workplace. Issue 5 (October 2020) - Crawford, Joanne O.; Berkovic, Danielle; Erwin, Jo; Copsey, Sarah M.; Davis, Alice; Giagloglou, Evanthia; Yazdani, Amin; Hartvigsen, Jan; Graveling, Richard; Woolf, Anthony
Abstract: Musculoskeletal (MSK) problems remain the most frequent reason why individuals are absent from work, including those with work-related musculoskeletal disorders (WRMSDs or MSDs) and those with chronic MSK problems. This paper aims to examine changes in work and the workforce since 2000; how work impacts on chronic MSK conditions and how we can help people with these conditions to stay at work. While our knowledge of the causes of WRMSDs has increased since 2000, there has been limited workplace action in reducing exposure to hazards. A life course approach is needed as individuals of all ages are reporting MSK problems. How people work has also changed and informalisation of work contracts has increased with a perceived concurrent reduction in occupational safety and health (OSH) protection. Retaining people at work with MSK problems requires compliance with relevant safety, health and diversity legislation and a risk management approach. Good and open communication within the workplace and identification of other sources of support is also necessary. Considerations must be made at the individual level (internal motivation), organisational level (a supportive manager) and self-management of symptoms. Simple case examples are provided in the paper of what works in practice as well as a proposed research agenda. Increased awareness at all levels of society of MSK health is essential.